Mitochondrial disease is a common cause of severe cardiomyopathy in children. (4th April 2011) - Bates, M G D; Nesbitt, V; He, L; Brodlie, M; Kirk, R; Taylor, R W; McFarland, R
Abstract : Aims: Respiratory chain abnormalities have been documented in children with idiopathic cardiomyopathy undergoing diagnostic endomyocardial biopsy.1 Mitochondrial disease can present with isolated cardiomyopathy or prominent cardiac involvement in multisystem disease, but when present, the cardiac phenotype is often severe.2 We undertook a prospective study to assess the frequency and characteristics of mitochondrial disease in children undergoing orthotopic cardiac transplantation or implantation of ventricular assist device (VAD) for severe cardiomyopathy. Methods: Macrobiopsies from the left ventricle±paired skeletal muscle were obtained from consecutive children <16 years of age undergoing cardiac transplantation or VAD implantation between February 2009 and July 2010. Spectrophotometric analysis of respiratory chain complexes I-IV and sequential cytochrome c oxidase (COX)/succinate dehydrogenase (SDH) histochemistry were performed as previously described.3 Focused molecular genetic techniques were undertaken in patients with biochemical evidence of mitochondrial disease. Results: 30 patients (14 male) underwent first cardiac transplantation±VAD implantation, with a further four patients (1 male) undergoing VAD implantation only (overall mean age 5.9±1.0 years). Myocardial macrobiopsies were available from 71% (24/34) of patients with paired skeletal muscle samples in seven patients. Histochemical and biochemical analyses of cardiac muscle were abnormal in 13% (3/24) of patients. Sequential COX/SDH histochemistry revealed a mosaic pattern of COX-deficiency within the myocardium of two patients. Respiratory chain activities were abnormal in cardiac muscle homogenates from both patients, while abnormalities were also detected in a third patient who had normal histochemistry. Molecular genetic testing is ongoing, but no pathogenic mtDNA mutations were identified in patients with histochemical abnormalities. Conclusion: Mitochondrial disease is common in children with severe cardiomyopathy, and may present as isolated cardiomyopathy or multisystem disease, yet the diagnosis was considered prior to myocardial tissue analysis in only one patient in this study. Given the potential tissue-specific nature of mitochondrial disease, investigation of myocardial tissue should be considered in all children with cardiomyopathy undergoing invasive cardiac procedures.